Pengaruh Rotasi Kerja, Lingkungan kerja dan Motivasi Spiritual Terhadap Kinerja Pegawai Amil di BAZNAS Kota Tanjungpinang (International Forum of Researchers and Lecturers, 2026)
This study aims to examine the effect of job rotation, physical work environment, and spiritual motivation on the performance of amil employees at BAZNAS Tanjungpinang City. This research adopts a quantitative approach using a survey method. The population consists of all amil employees at BAZNAS Tanjungpinang City totaling 35 respondents, and a census sampling technique is applied. Data were collected through questionnaires and analyzed using multiple linear regression with SPSS version 27. The partial test results indicate that job rotation and the physical work environment do not have a significant effect on amil employees’ performance. In contrast, spiritual motivation has a positive and significant effect on performance. Simultaneously, job rotation, physical work environment, and spiritual motivation collectively have a significant effect on the performance of amil employees at BAZNAS Tanjungpinang City. These findings highlight the important role of spiritual motivation in improving employee performance, particularly within zakat institutions that are strongly grounded in Islamic values.